1999
DOI: 10.1016/s0735-1097(98)00661-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of regional and global left ventricular function by reinjection Tl-201 and rest Tc-99m sestamibi ECG-gated SPECT

Abstract: Reinjection- and MIBI-g-SPECT provide clinically satisfactory various functional data. These functional data in combination with the perfusion information will improve diagnostic and prognostic accuracy without an increase in cost or the radiation dose to the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
61
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(69 citation statements)
references
References 19 publications
7
61
1
Order By: Relevance
“…The resultant temporal resolution of 21–42 ms was provided according to the individual heart rate. Cine MR images of 10–12 contiguous sections, 8 mm thick, with an interslice gap of 2 mm were obtained in the short-axis planes, covering the entire left ventricle from the base to the apex, to acquire 3-dimensional LV data [15,16,17]. In addition, cine MR images were acquired in the vertical and horizontal long-axis planes.…”
Section: Methodsmentioning
confidence: 99%
“…The resultant temporal resolution of 21–42 ms was provided according to the individual heart rate. Cine MR images of 10–12 contiguous sections, 8 mm thick, with an interslice gap of 2 mm were obtained in the short-axis planes, covering the entire left ventricle from the base to the apex, to acquire 3-dimensional LV data [15,16,17]. In addition, cine MR images were acquired in the vertical and horizontal long-axis planes.…”
Section: Methodsmentioning
confidence: 99%
“…In spite of this, it has been validated against other modalities (cMRI and first pass ERNA) [8]. Also Iskandarian et al [19] and Tadamura [20] found a good correlation between gated SPECT and cMRI in patients with myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Today, this modality provides multiplane dynamic images of the beating heart with excellent spatial resolution and temporal resolution of 30 phases per cardiac cycle, which is comparable to what has been for many years the standard frame rate in 2D echocardiography. The combination of these features places CMR imaging as the tentative "gold standard" for LV size and function, as reflected by multiple publications in which it was used as such to validate other noninvasive techniques (3)(4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…trast resolution that has become the standard reference in the assessment of left ventricular (LV) size and function (1,2), against which other techniques are frequently validated (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). However, this technique relies on the detection of endocardial boundaries, which requires frame-by-frame manual tracing on multiple slices, and is thus of limited value in clinical practice.…”
mentioning
confidence: 99%